If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8.2x = -41x + 131.2 Reorder the terms: -8.2x = 131.2 + -41x Solving -8.2x = 131.2 + -41x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '41x' to each side of the equation. -8.2x + 41x = 131.2 + -41x + 41x Combine like terms: -8.2x + 41x = 32.8x 32.8x = 131.2 + -41x + 41x Combine like terms: -41x + 41x = 0 32.8x = 131.2 + 0 32.8x = 131.2 Divide each side by '32.8'. x = 4 Simplifying x = 4
| -6.11-2.9n=-0.3n+2.1n | | 5-3v=4v+33 | | 17x-4=8x-22 | | -2x=13 | | -2=13 | | 1=2x+5 | | 6v=-6 | | 4=2z | | 5(1+3m)-(71+8m)=-671-9m-2(1-18m)=0 | | 8y-3y=-2 | | 4x^2=224 | | 4y-(y-4)=20 | | 2.6+1.7x=3.5+2x | | 2y+7y=36 | | 9w+6=6w-15 | | -26=6t-2 | | 5(1+3m)-(71+8m)=-6 | | 5p=15p | | 5(1+3h)-(71+8m)=-6 | | 8y-(-18)=2 | | 5(1+3m)*(71+8m)=-6 | | 5(1+3h)*(71+8m)=-6 | | 3x^3-15x^2+18=0 | | 2b-5=2b-5 | | 35=7t | | 6x^2+5x-14=0 | | 4(x+1)+4x=2(3x-1) | | 17-3(5-2x)=8+4x | | 6(36-10b)+8=32 | | 4(y-8)=-8 | | 5+3(4-3d)+6d=-7 | | 5+a=6+a |